2016
DOI: 10.1177/2047487316639681
|View full text |Cite
|
Sign up to set email alerts
|

The telephone lifestyle intervention ‘Hartcoach’ has modest impact on coronary risk factors: A randomised multicentre trial

Abstract: Hartcoach has modest impact on BMI, waist circumference, physical activity, intake of vegetables, self-management and anxiety. Therefore, it may be a useful maintenance programme in addition to usual care, to support patients with recent coronary events to improve self-management and reduce risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 24 publications
0
28
1
2
Order By: Relevance
“…In total, 11 studies about lipid changes , 11 studies about blood pressure , eight studies about smoking cessation , 13 studies about physical activity , eight studies about medication adherence and four studies about waist circumference were eventually included (summary of study characteristics) (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 11 studies about lipid changes , 11 studies about blood pressure , eight studies about smoking cessation , 13 studies about physical activity , eight studies about medication adherence and four studies about waist circumference were eventually included (summary of study characteristics) (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies were published between 2015 and 2017, and ten studies between 2003 and 2014. Four studies were conducted in Australia , four in the United States , three in Canada , two each in New Zealand , Sweden and Norway , and one in each of the following countries: Belgium , Italy , Malaysia , Netherlands , Germany , Korea and Iceland .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A RCT on telephone coaching for behaviour change in patients after acute coronary syndrome (ACS) has shown significant though modest effects on BMI, waist circumference, PA and daily intake of vegetables. 99 A RCT showed the effectiveness of a Web-based health behaviour change support system and group lifestyle counselling on body weight loss in overweight and obese subjects. 100 A systematic review on internet-delivered interventions in patients with CAD has shown that personalised, concrete support for behaviour change may have favourable outcomes; however, a considerable heterogeneity between studies with respect to the design and quality hinder sound conclusions.…”
Section: Behaviourmentioning
confidence: 99%
“…The CR goal in patients with ACS to improve emotional health may be reached through extended interventions that provide additional emotional support 17. Indeed, per-protocol analysis showed lower anxiety scores for patients in the CR+F group compared with the CR-only group and quality of life improvement in the CR+F group compared with the CR-only group.…”
Section: Discussionmentioning
confidence: 99%